2017
DOI: 10.1002/14651858.cd007078.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based interventions for smoking cessation

Abstract: The evidence from trials in adults suggests that interactive and tailored Internet-based interventions with or without additional behavioural support are moderately more effective than non-active controls at six months or longer, but there was no evidence that these interventions were better than other active smoking treatments. However some of the studies were at high risk of bias, and there was evidence of substantial statistical heterogeneity. Treatment effectiveness in younger people is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
219
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(271 citation statements)
references
References 220 publications
19
219
0
7
Order By: Relevance
“…Online resources had a low level of salience and appeared to be rarely used by interviewees. Given that tailored cessation support offered through internet‐based resources has been found to improve the likelihood of successful quit attempts among the general population, 27 this option may represent an underused alternative that could be the focus of future interventions. Access to technology is not necessarily a major barrier, as Australians experiencing homelessness have high rates of mobile phone use and approximately three‐quarters have access to a smartphone; however, data charges may be a possible barrier to use if public Wi‐Fi hotspots are unavailable 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Online resources had a low level of salience and appeared to be rarely used by interviewees. Given that tailored cessation support offered through internet‐based resources has been found to improve the likelihood of successful quit attempts among the general population, 27 this option may represent an underused alternative that could be the focus of future interventions. Access to technology is not necessarily a major barrier, as Australians experiencing homelessness have high rates of mobile phone use and approximately three‐quarters have access to a smartphone; however, data charges may be a possible barrier to use if public Wi‐Fi hotspots are unavailable 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Many groups exist, such as the American Lung Association's Freedom from Smoking program (http://www.lung.org/stop-smoking/join-freedomfrom-smoking/). Cochrane reviews have also shown effectiveness for telephone quit lines [37] and web-based interventions [38]. Oncologists in the United States with limited referral options for smoking cessation treatment can direct their patients to resources such as 1-800-QUIT-NOW or smokefree.gov.…”
Section: Treating the Biopsychosocial Aspects Of Tobacco Use And Addimentioning
confidence: 99%
“…Finally, lack of biochemical validation of smoking abstinence is a limitation that may have resulted in an overestimation of smoking abstinence [55]. However, a Cochrane review of lowintensity internet-based interventions for smoking cessation found that very few studies used biochemical validation given the difficulties in obtaining samples from participants [56] and expert consensus suggests that biochemical verification of abstinence is impractical and unnecessary in large studies such as the current one due to cost considerations and limited faceto-face contact [57]. Further, accurate estimates of the prevalence of cigarette smoking among Canadians can be derived from self-reported smoking status data [58].…”
Section: Limitationsmentioning
confidence: 99%